Nihilism and violence: Max Stirner’s case - Feć, Karolina (Hybris, 2016)
The paper presents a relation between nihilism and violence by using the theory of Max Stirner. The author’s choice of the philosopher is driven by her view that nihilism has reached its maturity in his main work. Even more, a key critique raised with respect to the author of "The Ego and his Own" touched exactly on the issue of violence (among others, in deliberations of Dostoyevsky and Camus). The study represents a polemic with the opinions presented in "The Rebellious Man", that Stirner glorified aggression and justified crime. Misreading of his philosophy, the philosophy of egoism, is founded in mixing might with violence which in fact are in that theory irreconcilable. Stirner's affirmation refers to the former whereas he is ambivalent to the latter.